Target Torque Control of Two-speed DCT Clutch based on GA-LQR - Zhang Zhigang; Chen Jinjing; Yao Lianhong; Zheng Yanjie (Jixie chuandong)
For an electric vehicles equipped with two-speed dual clutch transmission (DCT)， the two sets of clutch target torques are coordinated during the shifting process in order to obtain a more comfortable shifting quality. Regarded impact degree and the specific sliding friction work as evaluation indictor， and taking the impact degree and the sliding work as quadratic target functions， the Linear Quadratic Regulator (LQR) method is used to determine the clutch target torque of the torque phase of the shifting process. The global search ability of the genetic algorithm (GA) is used to optimally select the weighting matrix in the LQR. Thereby， the clutch target torque of better shift quality is obtained. Finally， the target torque of fixed slope change clutch currently used in the two-speed DCT is compared with the clutch target torque determined by this method. The result shows that the latter takes less time during the shifting process， and both the impact degree and the sliding friction work are reduced. The shifting quality of the two-speed DCT is improved effectively.